To complete the square for the quadratic equation \( x^2 - 2x - 1 = 0 \), we first focus on the expression \( x^2 - 2x \).
To complete the square, we follow these steps:
- Take the coefficient of \( x \), which is \(-2\).
- Divide it by 2: \(-2 / 2 = -1\).
- Square the result: \((-1)^2 = 1\).
Now, to complete the square, we need to add \(1\) to the expression. So, you would add \(1\) to both sides of the equation:
\[ x^2 - 2x + 1 = 1 - 1 \]
This gives us:
\[ (x - 1)^2 = 0 \]
Thus, to complete the square, you would add \(1\).